Size matters: micro-evolution in Polynesian rats highlights body size changes as initial stage in evolution - Alexandra A.E. van der Geer (PeerJ, 2020)
Microevolutionary patterns in populations of introduced rodent species have often been the focus of analytic studies for their potential relevance to understanding vertebrate evolution. The Polynesian rat (Rattus exulans) is an excellent proxy species because of its wide geographic and temporal distribution: its native and introduced combined range spans half the globe and it has been living for at least seven centuries wherever it was introduced. The objective of this study was to assess the effects of long-term isolation (insularity; up to 4,000 years) and geographic variables on skull shape variation using geometric morphometrics. A sample of 513 specimens from 103 islands and four mainland areas was analysed. This study, to my knowledge the first to extensively sample introduced rats, analysed 59 two-dimensional landmarks on the skull. Landmarks were obtained in three separate aspects (dorsal, lateral, ventral skull view). The coordinate data were then subjected to a multivariate ordination analysis (principal components analysis, or PCA), multivariate regressions, and a canonical variates analysis (CVA). Three measures of disparity were evaluated for each view. The results show that introduced Polynesian rats evolve skull shapes that conform to the general mammalian interspecific pattern of cranial evolutionary allometry (CREA), with proportionally longer snouts in larger specimens. In addition, larger skulls are more tubular in shape than the smaller skulls, which are more balloon-shaped with a rounder and wider braincase relative to those of large skulls. This difference is also observed between the sexes (sexual dimorphism), due to the slightly larger average male size. Large, tubular skulls with long snouts are typical for Polynesia and Remote Oceania, where no native mammals occur. The greater disparity of Polynesian rats on mammal species-poor islands (’exulans-only’ region) provides further insight into how diversity may affect diversification through ecological release from predators and competitors.